John Steinbeck's Of mice and men - Bloom, Harold (Broomall, PA : Chelsea House Publishers, 1996)
Includes a brief biography of John Steinbeck, thematic and structural analysis of the work, critical views, and an index of themes and ideas.
"A Contemporary Literary Views book.".
"Books by John Steinbeck": p. 56-58.
Includes bibliographical references (p. 59-61) and index.
Book Report.
Young Adult
Keywords: Steinbeck, John, -- 1902-1968.; Steinbeck, John, -- 1902-1968.; Cowboys in literature; Friendship in literature; American literature -- History and criticism; Salinas River Valley (Calif.) -- In literature